1985
DOI: 10.1002/j.1939-4640.1985.tb00822.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Serum Levels of LH, FSH, Prolactin, Testosterone, and Cortisol Associated with Season and Mating in Male Pygmy Goats

Abstract: Four male pygmy goats were used in a study designed to determine the effects of season on serum hormone (luteinizing hormone, follicle stimulating hormone, prolactin, testosterone, and cortisol) levels, testis size and libido, and the effects of mating on serum hormone profiles. Seasonal peaks were observed for prolactin in July, luteinizing hormone and follicle stimulating hormone in September, and testosterone in October. Luteinizing hormone peak frequency was greatest in September and was increased by matin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
11
1
1

Year Published

1994
1994
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 24 publications
5
11
1
1
Order By: Relevance
“…The significant decrease in PCV from pre-treatment to posttreatment is at variance with the finding of Eniolorunda et al (2006) who opined that Spondias mombin leaves fed to growing bucks for 63 days had no significant effect on PCV but their work was in agreement with the non-significant effect on WBC recorded in this work. At variance with this work, pronounced post-treatment testosterone concentration of 5.56 ± 4.72 ng/ml in this work was slightly higher than 5.00ng/ml recorded by Howland et al (1985) who worked around similar period of the year (August) on intact normal pygmy goats while still kept away from mating. These workers also recorded 40ng/ml as prolactin concentration for the pygmy goats which was higher than 10.74 ± 4.77ng/ml reported in this work for pre-treatment and 25.80 ± 41.50ng/ml for post-treatment.…”
Section: Discussioncontrasting
confidence: 70%
“…The significant decrease in PCV from pre-treatment to posttreatment is at variance with the finding of Eniolorunda et al (2006) who opined that Spondias mombin leaves fed to growing bucks for 63 days had no significant effect on PCV but their work was in agreement with the non-significant effect on WBC recorded in this work. At variance with this work, pronounced post-treatment testosterone concentration of 5.56 ± 4.72 ng/ml in this work was slightly higher than 5.00ng/ml recorded by Howland et al (1985) who worked around similar period of the year (August) on intact normal pygmy goats while still kept away from mating. These workers also recorded 40ng/ml as prolactin concentration for the pygmy goats which was higher than 10.74 ± 4.77ng/ml reported in this work for pre-treatment and 25.80 ± 41.50ng/ml for post-treatment.…”
Section: Discussioncontrasting
confidence: 70%
“…There is no evidence, however, for elevated cortisol levels being connected to the high testosterone levels per se during the reproductively active period of male goats (Howland et al, 1985), sheep (Lincoln et al, 1982), or white-tailed deer (Bubenik et al, 1983), although a parallel acute rise of both hormones occurs during sexual and aggressive behavior (Howland et al, 1985;Liptrap and Raeside, 1978). On the contrary, in some studies higher cortisol levels in male deer have been found during the sexually inactive rather than the active period of the year (Bubenik et al, 1983;Ingram et al, 1999;Monfort et al, 1993).…”
Section: Discussionmentioning
confidence: 80%
“…The direction of the change and not the photoperiod as such seemed to affect the cortisol levels. We are aware only of one previous study that has addressed seasonal variations of goat serum cortisol concentrations (Howland et al, 1985). Four male pygmy goats were sampled each month of the year for 6 h at 20min intervals, and the samples were pooled for hormone measurements.…”
Section: Discussionmentioning
confidence: 99%
“…This may reflect the different latitudes at which the two studies were done (40°N v. 50° 46') or the method used to assess testicular size; in the French study testicular volume was estimated using an orchidometer and the results subsequently converted to, and reported as, a testicular weight. Similarly, in a study involving four mature pygmy bucks over a 13-month period in southern Canada, Howland et al (1985) reported no seasonal influence on testis size or libido, despite there being significant changes in peripheral testosterone concentration, with the highest values recorded in the autumn. However, that study was based on data from six animals ranging in age from 10 months to 6 years and for a relatively short period of time viz.…”
Section: Discussionmentioning
confidence: 92%